Heel-toe running: A new look at the influence of foot strike pattern on impact force - John A. Mercer; Sarah Horsch (Elsevier, 2015)
Background/Objective: It is important to understand the factors that influence the impact force observed during running, since the impact force is likely to be related to overuse injuries. The purpose of this study was to compare the impact force during running when participants were instructed to use different foot strike patterns: obvious heel strike (Obvious-HS), subtle heel strike (Subtle-HS), midfoot strike (Mid-FS), and fore foot strike (Fore-FS) patterns. Methods: Participants (n = 10, 25 ± 5.7 years, 70.2 ± 12.1 kg, 174.6 ± 7.2 cm) completed four foot strike patterns while running over ground: Obvious-HS, Subtle-HS, Mid-FS, and Fore-FS. Speed was controlled between conditions (random order). Vertical ground reaction forces were recorded (1000 Hz) along with the impact force, peak force, and stance time for analysis. A repeated measures analysis of variance was used to compare each variable across foot strike instructions, with post hoc comparisons contrasting Obvious-HS to each of the other conditions. Results: Impact force was influenced by foot strike instructions, with Obvious-HS being greater than Subtle-HS and Fore-FS (p < 0.05) but not different from Mid-FS (p > 0.05). The peak force was not influenced by foot strike instructions (p > 0.05); stance time was longer during Obvious-HS than during Mid-FS or Fore-FS (p < 0.05), but not different from Subtle-HS (p > 0.05). Conclusion: The unique observation of this study was that impact force was different when participants were instructed to run with either an Obvious-HS or a Subtle-HS at contact. Both these foot strike patterns would have been considered rear foot strike patterns, suggesting that something other than which specific part of the foot strikes the ground initially influenced impact force.